1997
DOI: 10.1507/endocrj.44.419
|View full text |Cite
|
Sign up to set email alerts
|

Increased Circulating Levels of Insulin-Like Growth Factor-I and Decreased Circulating Levels of Insulin-Like Growth Factor Binding Protein-1 in Postmenopausal Women with Endometrial Cancer.

Abstract: Abstract. In human endometrium insulin-like growth factor binding protein (IGFBP)-1 inhibits the mitogenic action of insulin-like growth factor (IGF)-I by inhibiting the binding of IGF-I to its receptor. Our purpose was to compare circulating levels of IGF-I and IGFBP-1 in women with and without endometrial cancer. We assessed circulating levels of IGF-I and IGFBP-1 and IGFBP-3 in 23 patients with endometrial cancer, 11 patients with uterine cervical cancer and 27 healthy control women. The mean circulating le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 23 publications
(14 reference statements)
2
43
0
4
Order By: Relevance
“…Ayabe et al (35), in a small study of 11 cervical cancer patients and 27 controls, found not significant association between serum levels of IGF-I and cervical cancer risk.…”
Section: Discussionmentioning
confidence: 94%
“…Ayabe et al (35), in a small study of 11 cervical cancer patients and 27 controls, found not significant association between serum levels of IGF-I and cervical cancer risk.…”
Section: Discussionmentioning
confidence: 94%
“…Ayabe ve ark. 17 tarafından yapılan çalışmada endometrium kanserli kadınların serum IGF-1 düzey-lerinin kontrol grubuna nazaran daha yüksek olduğu saptanmıştır. Bu bulgu da obezite, DM ve HT varlığının …”
Section: Discussionunclassified
“…However, these studies are scarce and the results remain inconsistent (Table 3) [10,[28][29][30][31][32][33][34][35]. Four studies found no association between serum IGF-1 and EC biology [10,[28][29][30].…”
Section: Serum Igf-1 and Endometrial Cancermentioning
confidence: 99%